The Correlation of Vocabulary Mastery on Students’ Speaking Ability - Kunah Kunah; Supriyani Supriyani; Handoko Handoko (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2026)
The purpose of this study is to determine the relationship between students' proficiency with vocabulary and their capacity to speak, as well as to gather evidence that this association is substantial. This research methodology is a kind of non-experimental research that employs quantitative techniques with a correlational model. The study was carried out on students in class VIII at SMPN 1 Kroya. Out of the 305 students in class VIII, a sample of 62 students or two classes were chosen; consequently, a cluster random sampling technique was utilized in the chosen classes. Tests of learning outcomes, documentation, English comprehension skills, and research instruments were used to gather research data throughout learning activities. A correlation test utilizing Pearson Product Moment Correlation is performed once all the analysis findings are normally distributed. The study's findings indicate a relationship between class VIII at SMPN 1 Kroya's speaking abilities and vocabulary mastery. The lowest scores for students' vocabulary mastery and speaking ability exams were 24 and 25 points. A correlation coefficient value of 0.969 was derived using the SPSS 23 program's computations. This indicates a strong correlation between the two variables, with a significance value (2-tailed) of 0.000. The alternative hypothesis (Ha) is accepted if the significance test result is Sig < 0.05 (0.000 < 0.05). The alternative hypothesis (Ha) is then accepted and the null hypothesis (Ho) is rejected, indicating that there is a connection between students' speaking proficiency at SMPN 1 Kroya and their vocabulary competence.